Drought-Induced Root Pressure in Sorghum bicolor - Drobnitch, Sarah Tepler; Comas, Louise H.; Flynn, Nora; Ibarra Caballero, Jorge; Barton, Ryan W.; Wenz, Joshua; Person, Taylor; Bushey, Julie; Jahn, Courtney E.; Gleason, Sean M. (Frontiers in Plant Science, 2021)
Root pressure, also manifested as profusive sap flowing from cut stems, is a phenomenon in some species that has perplexed biologists for much of the last century. It is associated with increased crop production under drought, but its function and regulation remain largely unknown. In this study, we investigated the initiation, mechanisms, and possible adaptive function of root pressure in six genotypes of Sorghum bicolor during a drought experiment in the greenhouse. We observed that root pressure was induced in plants exposed to drought followed by re-watering but possibly inhibited by 100% re-watering in some genotypes. We found that root pressure in drought stressed and re-watered plants was associated with greater ratio of fine:coarse root length and shoot biomass production, indicating a possible role of root allocation in creating root pressure and adaptive benefit of root pressure for shoot biomass production. Using RNA-Seq, we identified gene transcripts that were up- and down-regulated in plants with root pressure expression, focusing on genes for aquaporins, membrane transporters, and ATPases that could regulate inter- and intra-cellular transport of water and ions to generate positive xylem pressure in root tissue.